Evaluating the Outcomes of Surgical Versus Conservative Treatments in Head Injury: A Comparative Observational Study Using Different Scales - Sunny, Sanisha; Vajjapally, Priyanka; Bhava Bandaru, Sheshagiri Sharavana; EggadI, Venkateshwarlu; Kulandaivelu, Umasankar; Bandari, Rajamohan (Indian Journal of Pharmacy Practice)
Background: This study is to evaluate the outcomes of surgical versus conservative treatment in head injury by using different scales to rate the quality of life in both the treatments. Aim: To evaluate the outcomes of surgical versus conservative treatment in Head injury. Methods: A prospective, comparative observational study was conducted in Neurosurgery department in a tertiary care teaching hospital for a period of 6 months. All the patients with head injury were included in the study and reviewed.Among the subjects two groups are made in which one group includes the subjects who are treated with conservative treatment and the other group who have undergone surgical treatment among these two groups GCS scale, four score scale and dementia rating scale are assessed and both the treatments are compared. Results: Patients with head injury between age groups of 20 to 70 years were recruited for this study. The patients recovery analysis according to GCS for conservative (93.06%) and surgical (50.40%), FSS for conservative (90%) and surgical (56.75%), DRS for conservative (100%) and surgical (50.04%). Conclusion: Based on the severity it is decided whether conservative or surgical treatment is given to the patient, but primary choice of treatment should be conservative treatment for patients with less severity as patients under conservative treatment had better recovery and memory compared to that of patients under surgical treatment.
Keywords: Head injury; Glasgow scale; FOUR score scale; Dementia rating scale; Surgical; conservative.